2015 IEEE 82nd Vehicular Technology Conference (VTC2015-Fall) 2015
DOI: 10.1109/vtcfall.2015.7391146
|View full text |Cite
|
Sign up to set email alerts
|

Soft Handover in OFDMA Based Visible Light Communication Networks

Abstract: As the demand for wireless bandwidth rapidly increases, alternative methods to radio frequency-based communication are investigated to overcome the limited bandwidth problem. Visible light communication (VLC) using light emitting diodes (LEDs) is one of these alternatives. LEDs are estimated to replace the incandescent bulbs within the decade. Since, LEDs can be intensity modulated faster than the human eye can detect, illumination and communication can both be provided by the same lighting system. Indoors com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Optical OFDMA (O-OFDMA) was proposed in [194] which has a lower decoding complexity and power efficiency in comparison with O-OFDM based interleave division multiple access (IDMA). In [195], the authors have considered two handover schemes for users within the intersection area of two optical transmitters: In the first scheme, the user combines the signal of both transmitters, while in the second scheme the each transmitter use a dedicated band for the user. IFDMA was proposed in [196] to mitigate the high PAPR effects of O-OFDMA where it was shown that IFDMA have lower computational complexity than O-OFDMA and it reduces the synchronization errors.…”
Section: Multiple Access Schemesmentioning
confidence: 99%
“…Optical OFDMA (O-OFDMA) was proposed in [194] which has a lower decoding complexity and power efficiency in comparison with O-OFDM based interleave division multiple access (IDMA). In [195], the authors have considered two handover schemes for users within the intersection area of two optical transmitters: In the first scheme, the user combines the signal of both transmitters, while in the second scheme the each transmitter use a dedicated band for the user. IFDMA was proposed in [196] to mitigate the high PAPR effects of O-OFDMA where it was shown that IFDMA have lower computational complexity than O-OFDMA and it reduces the synchronization errors.…”
Section: Multiple Access Schemesmentioning
confidence: 99%
“…In [9] a handover procedure was proposed based on a pre-handover scheme that relies on position estimation obtained by visible light positioning and motion tracking with Kalman filters. In [10] power and frequency-based soft handover methods were proposed to reduce data rate fluctuations as the mobile device moves from one cell to another. The statistical distribution of the received data rate was also studied using computer simulations.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed system achieves both hard-link switching and soft-link switching reward without exchanging device hardware and the IEEE 802.15.7 medium access control (MAC) protocol. Because the hard handover may result in lost data connection, a soft handover scheme was presented in [17] by using orthogonal frequency division multiple access (OFDMA) under mobility. Wang et al [4] investigated a Markov decision process problem and implemented a dynamic method to obtain a trade-off between the cost of switching and the delay requirement.…”
Section: Related Workmentioning
confidence: 99%
“…In this instance, the handover cost is determined largely by the mean blocking time γ 2 and handover delay. However, when handover is not executed (a(s) = 0), the expected cost is represented as g(s, a(s)) = γ 2 f VLC→BLOCK (17) The handover delay cost is determined by the handover delay, which is the waiting time in the uplink and downlink queue plus the packet processing time. For example, if the UE triggers a handover from the VLC to RF network, it first sends an access request via the RF uplink queue.…”
Section: Handover Penalty Functionmentioning
confidence: 99%